Why study the use of animal products in traditional medicines? - Rosa Ierecê L; Alves Rômulo RN (BMC, 2005)
Abstract The World Health Organization (WHO) estimates that as many as 80% of the world's more than six billion people rely primarily on animal and plant-based medicines. The healing of human ailments by using therapeutics based on medicines obtained from animals or ultimately derived from them is known as zootherapy. The phenomenon of zootherapy is marked both by a broad geographical distribution and very deep historical origins. Despite their importance, studies on the therapeutic use of animals and animal parts have been neglected, when compared to plants. This paper discusses some related aspects of the use of animals or parts thereof as medicines, and their implications for ecology, culture (the traditional knowledge), economy, and public health.